1949
DOI: 10.1021/j150466a006
|View full text |Cite
|
Sign up to set email alerts
|

Suspension of Manganese Dioxide in Detergents.

Abstract: The controlled formation of stable dispersions of solid powders in liquids is of both theoretical and practical interest. The suspendibility of a powder depends upon and aids in the understanding of the surface properties of the disperse phase, as these affect, cohesion between particles in various media and as they result, in selective adsorption of ions or molecules from solution. Moreox-er many commercial products, such as paints and printing inks, consist of finely clix idecl solids dispersed in liquids. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
61
2

Year Published

1962
1962
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 11 publications
9
61
2
Order By: Relevance
“…The value for C2H6 agrees well with both the recommended value and the value of Greiner (16). The reported values for C3H, (16,21,22) differ by over a factor of 2.…”
Section: Comparison Of Rate Constant Valuessupporting
confidence: 80%
See 2 more Smart Citations
“…The value for C2H6 agrees well with both the recommended value and the value of Greiner (16). The reported values for C3H, (16,21,22) differ by over a factor of 2.…”
Section: Comparison Of Rate Constant Valuessupporting
confidence: 80%
“…The value for C2H6 agrees well with both the recommended value and the value of Greiner (16). The reported values for C3H, (16,21,22) differ by over a factor of 2. Our value agrees well with the higher value of Gorse and Volman (22), determined indirectly, relative to the rate constant of the reaction OH + CO. For personal use only.…”
Section: Comparison Of Rate Constant Valuessupporting
confidence: 80%
See 1 more Smart Citation
“…The rate coefficients from these studies Baker et al, 1970;Baldwin and Walker, 1979;Hucknall et al, 1975; are fitted to the three parameter expression, k=CT 2 exp(-D/T ), resulting in k=1.81×10 −17 T 2 exp(114/T ) cm 3 molecule −1 s −1 over the temperature range 230-760 K. The preferred Arrhenius expression, k=A exp(-B/T ), is centered at 260 K and is derived from the three parameter expression with A = Ce 2 T 2 and B = D + 2T . The preferred values are in good agreement with the room temperature absolute and relative rate coefficients of Greiner (1970), Stuhl (1973, , Paraskevopoulos and Nip (1980), , , , , Barnes et al (1986), Behnke et al (1988) and Chuong and Stevens (2002), which were not used in the evaluation of the rate coefficient.…”
Section: Comments On Preferred Valuessupporting
confidence: 57%
“…Preferred values are based on an average of the data from , Kuo and Lee (1991), Fulle et al (1997), Chuong and Stevens (2000), Klein et al (1984), Atkinson (1994, Davis et al (1975), Howard (1976, Greiner (1970), Morris et al (1971), Overend and Paraskevopoulos (1977), Atkinson et al (1977), , Cox (1975) and Vakhtin et al (2003), where the latter work showed the lowest scatter and, therefore, is given the highest weight. Falloff curves are constructed with the calculated F c =0.48 from Fulle et al (1997).…”
Section: Comments On Preferred Valuesmentioning
confidence: 99%